2013
DOI: 10.1242/jeb.077420
|View full text |Cite
|
Sign up to set email alerts
|

Development of apical membrane organization and V-ATPase regulation in blowfly salivary glands

Abstract: SUMMARYSupplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Recent work in mosquito tubules has demonstrated that cAMP stimulates both V-ATPase activity and assembly of the holoenzyme (Tiburcy et al, 2013), which supports the findings in other insects [e.g. the blowfly (Baumann and Bauer, 2013)] and in other systems (Bond and Forgac, 2008). Although it is also possible that cyclic nucleotide kinases such as protein kinase A (PKA) may act to phosphorylate modulatory proteins for the V-ATPase, how may cyclic nucleotides increase the transepithelial potential difference across tubule principal cells?…”
Section: Cyclic Nucleotide Signallingsupporting
confidence: 76%
“…Recent work in mosquito tubules has demonstrated that cAMP stimulates both V-ATPase activity and assembly of the holoenzyme (Tiburcy et al, 2013), which supports the findings in other insects [e.g. the blowfly (Baumann and Bauer, 2013)] and in other systems (Bond and Forgac, 2008). Although it is also possible that cyclic nucleotide kinases such as protein kinase A (PKA) may act to phosphorylate modulatory proteins for the V-ATPase, how may cyclic nucleotides increase the transepithelial potential difference across tubule principal cells?…”
Section: Cyclic Nucleotide Signallingsupporting
confidence: 76%
“…3 ). Finally, the central hub occupied by the V-ATPases in the predicted PPI network is noteworthy because these electrolyte/solute trans-epithelia transporters are critical in saliva secretion in other insects such as the blowflies [ 69 ]. Trypanosoma.…”
Section: Discussionmentioning
confidence: 99%
“…cockroaches) while previous studies have shown serotonin to be the neurohormone activating saliva production ( Röser et al. 2012 ; Baumann and Bauer 2013 ). In a previous report ( Guerra et al.…”
Section: Discussionmentioning
confidence: 97%
“…(1995) on Aedes aegypti . We would like to emphasize here that the studies in the Diptera have focused on control of saliva production ( Baumann and Bauer 2013 ) and not on salivation release. The presence of muscles surrounding the secretory regions of the sgld in tsetse might be a mechanism for rapidly dispensing the saliva into the host, thus avoiding a host response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation